Determination of Students ' Knowledge Using a Non-Standard Test When Teaching the Subject of the Document (Texas Journal of Engineering and Technology, 2022)
The article is devoted to the issues of using non-standard tests in strengthening the cognitive activity of students when teaching the topic “Khojaly” in biology.